2020
DOI: 10.47992/ijmts.2581.6012.0110
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Industry 4.0 Readiness Model for Indian Engineering Industries

Abstract: For India to be a global economic superpower, the Indian Engineering Industry which at present is the largest foreign exchange earner must make its strong presence in the global markets. Industry 4.0 is one such initiative which has the power to transform the Indian Engineering Industry to be globally competitive along several strategic dimensions. Industry 4.0 is gradually making inroads and yet, there is no model to assess whether the Indian Engineering Industry is prepared to implement Industry 4.0. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In addition, some other skills such as creativity, problem-solving, teamwork and critical thinking are also required (Ras et al , 2017). Thus, for the successful application of Industry 4.0 in developing economies, training, skill development and upskilling are of prime importance (Sony and Aithal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some other skills such as creativity, problem-solving, teamwork and critical thinking are also required (Ras et al , 2017). Thus, for the successful application of Industry 4.0 in developing economies, training, skill development and upskilling are of prime importance (Sony and Aithal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sony and Aithal (2020) developed a multi-dimensional readiness model of Industry 4.0 by an in-depth review of the research literature, and then the model was qualitatively analyzed using the ABCD framework, and its advantages, disadvantages, and challenges were discussed. Grufman et al .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Nick et al (2019) and Grufman et al (2020) used the same dimensions to assess Industry 4.0 readiness in their studies. On the other hand, Trstenjak and Opetuk (2020) and Sony and Aithal (2020) analyzed the technical aspect of readiness using smart factory, smart operations, and smart products as the dimensions and the managerial aspect of readiness including strategy and organization, employees, leadership and culture as the dimensions. VMG model focused more on business models, products and services portfolio, value chain and legal considerations as well as strategy and organization, smart factory and smart products.…”
Section: Dimensions and Indicators Of The Industry 40 Readiness Modelmentioning
confidence: 99%
“…Despite positive experiences and benefits harnessed by companies and strong political will, there is very little acceptance of the I4.0 vision in reality. Past studies have found prominent barriers, like capital investment requirements and unclear cost-benefit analysis of the I4.0 applications (Sony and Aithal 2020), missing clearcut investment plans, lack of practical change management approach, lack of appropriate skills, lack of support from trade unions, lack of digital leadership, and unclear digital vision (Türkeş et al 2019) responsible to this low response from the industries. Moreover, inadequate internet connectivity, insufficient data protection, and IT infrastructure converge into extreme challenges, which may create havoc if not attended to at the right time while adopting I4.0 (Khanzode et al 2021;Luthra and Mangla 2018).…”
Section: Introductionmentioning
confidence: 99%